Reflections: Dieedra Welch, Emily Valle, Diego Camacho, Wilfredo Barrea - Welch, Dieedra; Valle, Emily; Camacho, Diego; Barrea, Wilfredo (Young Scholars Grinchenko – Seton International Journal, 2022)
Below are the reflections of 11th and 12th-grade students of the Collegiate Charter High School of Los Angeles, California, the USA about the online meeting "Stand with Ukraine". Students during the war: a virtual bridge with Kyiv, Ukraine" with students and teachers of Borys Grinchenko Kyiv University, Ukraine and Seton Hall University, New Jersey, the USA, which took place on April 5, 2022.